Atomic level description of the domain closure in a dimeric enzyme: thermus thermophilus 3-isopropylmalate dehydrogenase (IPMDH) - Graczer, E.; Merli, Angelo; Singh, R. K.; Karuppasamy, Manikandan; Zavodszky, P.; Weiss, M. S.; Vas, M. (FEBS Journal, 2011)

Mechanism of unfolding of human prion protein - Singh, R. K.; Chamachi, N. G.; Chakrabarty, S.; Mukherjee, A. (Journal of Physical Chemistry B, 2017)
Misfolding and aggregation of prion proteins are associated with several neurodegenerative diseases. Therefore, understanding the mechanism of the misfolding process is of enormous interest in the scientific community. It has been speculated and widely discussed that the native cellular prion protein (PrPC) form needs to undergo substantial unfolding to a more stable PrPC* state, which may further oligomerize into the toxic scrapie (PrPSc) form. Here, we have studied the mechanism of the unfolding of the human prion protein (huPrP) using a set of extensive well-tempered metadynamics simulations. Through multiple microsecond-long metadynamics simulations, we find several possible unfolding pathways. We show that each pathway leads to an unfolded state of lower free energy than the native state. Thus, our study may point to the signature of a PrPC*. form that corresponds to a global minimum on the conformational free-energy landscape. Moreover, we find that these global minima states do not involve an increased beta-sheet content, as was assumed to be a signature of PrPSc formation in previous simulation studies. We have further analyzed the origin of metastability of the PrPC form through free energy surfaces of the chopped helical segments to show that the helices, particularly H2 and H3 of the prion protein, have the tendency to form either a random coil or a beta-structure. Therefore, the secondary structural elements of the prion protein are only weakly stabilized by tertiary contacts and solvation forces so that relatively weak perturbations induced by temperature, pressure, pH, and so forth can lead to substantial unfolding with characteristics of intrinsically disordered proteins.